The Effects of Influent Debit on Hydrodynamic Characteristic of Bojongsoang Facultative Pond: Without Wind Effects - Hadisoebroto, Rositayanti; Notodarmojo, Suprihanto (UI Scholars Hub, 2004)
The Effects of Influent Debit on Hydrodynamic Characteristic of Bojongsoang Facultative Pond: Without Wind Effects. The performance of facultative pond in Bojongsoang WWTP have reported to be unstable. One of the cause of the unstable performance is the hydrodynamic characteristics that not met the criterion. The improper hydrodynamic characteristics are included the existence of dead-zone, the short-circuiting, and the turbulence due to eddy current. The study was to analyze the effect of the influent debit variation on the hydrodynamic characteristics of the pond using mathematical model. The two-dimensional hydrodynamic model was built from two hydrodynamic equations which are continuity and momentum equations. The equations were solved by finite-difference numerical method of semi-implicit (Crank-Nicolson). From the simulation results, the Froude number of the water flow was analyzed. Beside that, the effective residence time and the effective area were calculated. All of them were done to analyzed the existence of the dead-zone in the pond. The simulation results show that the dead-zone was exist in the center of the pond. when the influent debit was larger, the effective residence time and the effective area become larger. The distribution of the Froude number value shows that the area with the value of 10-10 become reduced in the larger influent debit. The existence of the dead-zone was reduced since the influent debit become larger. It can be said that the larger influent debit can improve the hydrodynamic characteristics of the pond.